2015
DOI: 10.4062/biomolther.2015.007
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Resistance to BRAF Inhibitor Is Associated with the Inability of Spry2 to Inhibit BRAF-V600E Activity in BRAF Mutant Cells

Abstract: The clinical benefits of oncogenic BRAF inhibitor therapies are limited by the emergence of drug resistance. In this study, we investigated the role of a negative regulator of the MAPK pathway, Spry2, in acquired resistance using BRAF inhibitor-resistant derivatives of the BRAF-V600E melanoma (A375P/Mdr). Real-time RT-PCR analysis indicated that the expression of Spry2 was higher in A375P cells harboring the BRAF V600E mutation compared with wild-type BRAF-bearing cells (SK-MEL-2) that are resistant to BRAF in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…It has been reported that activation of ERK leads to negative feedback regulation of MEK [ 30 ]. Our previous results also showed that long-term treatment with BRAF inhibitors significantly downregulated Spry2 in BRAF V600E–positive cell lines, and that this change is accompanied by rebound activation of the MAPK pathway [ 6 ]. As expected, the phospho-ERK levels were relatively unresponsive to PLX4720 in mimic-controltransfected A375P/Mdr cells.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…It has been reported that activation of ERK leads to negative feedback regulation of MEK [ 30 ]. Our previous results also showed that long-term treatment with BRAF inhibitors significantly downregulated Spry2 in BRAF V600E–positive cell lines, and that this change is accompanied by rebound activation of the MAPK pathway [ 6 ]. As expected, the phospho-ERK levels were relatively unresponsive to PLX4720 in mimic-controltransfected A375P/Mdr cells.…”
Section: Discussionmentioning
confidence: 93%
“…Because it is known that A375P/Mdr cells are resistant to BRAF inhibitor-induced ERK inhibition [ 6 ], we used immunoblotting to examine phospho-MEK and phospho-ERK levels in mimic-control-RNA–transfected and miR-1246–transfected A375P/Mdr cells after PLX4720 treatment ( Fig. 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it does not bind to or inhibit BRAF V600E and is instead upregulated in BRAF‐mutant melanoma cells . Sprouty2 is also related to the induction of resistance to BRAF inhibitor in BRAF‐mutant melanoma cells . Salmonella typhimurium strain VNP20009 harboring Sprouty2‐expressing plasmid suppresses the s.c. growth of B16F10, a murine melanoma cell line, in vivo…”
Section: Roles Of Sprouty/spred During Tumorigenesis and Metastasismentioning
confidence: 99%
“…2 Sprouty2 is also related to the induction of resistance to BRAF inhibitor in BRAF-mutant melanoma cells. 69 Salmonella typhimurium strain VNP20009 harboring Sprouty2-expressing plasmid suppresses the s.c. growth of B16F10, a murine melanoma cell line, in vivo. 70 The knockdown of Spred1 and Spred2 shows an effect similar to that of an MEK inhibitor and protects against apoptosis of BRAF V600E-positive melanoma cell lines.…”
Section: Sprouty/spred and Melanomamentioning
confidence: 99%